2007
DOI: 10.1007/s00248-006-9189-7
|View full text |Cite
|
Sign up to set email alerts
|

Diel and Seasonal Variations in Abundance, Activity, and Community Structure of Particle-Attached and Free-Living Bacteria in NW Mediterranean Sea

Abstract: Diel and seasonal variations in abundance, activity, and structure of particle-attached vs free-living bacterial communities were investigated in offshore NW Mediterranean Sea (0-1000 m). Attached bacteria were always less abundant and less diverse but generally more active than free-living bacteria. The most important finding of this study was that the activity of attached bacteria showed pronounced diel variations in the upper mixed water column with higher activities at night. Under mesotrophic conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
148
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(175 citation statements)
references
References 58 publications
24
148
1
2
Order By: Relevance
“…Bacterial production, in carbon units averaged about 29 mg C m −2 d −1 over the top 150 m of the water column , equivalent to 0.2 mg C m −3 , suggesting that bacterial production was very low relative to both total bacterial biomass and phytoplankton production. In contrast, periodically, a large portion (up to about 50%) of bacterial activity was associated with particleattached bacteria, as previously observed at the same sampling site under spring conditions (Ghiglione et al, 2007).…”
Section: The Microbial Loopsupporting
confidence: 80%
See 1 more Smart Citation
“…Bacterial production, in carbon units averaged about 29 mg C m −2 d −1 over the top 150 m of the water column , equivalent to 0.2 mg C m −3 , suggesting that bacterial production was very low relative to both total bacterial biomass and phytoplankton production. In contrast, periodically, a large portion (up to about 50%) of bacterial activity was associated with particleattached bacteria, as previously observed at the same sampling site under spring conditions (Ghiglione et al, 2007).…”
Section: The Microbial Loopsupporting
confidence: 80%
“…Below we will first very briefly review the cruise plan then highlight some of the findings described in detail in the individual papers of this special section. In the framework of the PECHE project, two additional shortcruises were conducted at the DYFAMED site in March and June 2003 (Garcia et al, 2006;Ghiglione et al, 2007;Bourguet et al, 2009) whose results are used as spring and early summer reference in several individual papers of this special issue.…”
mentioning
confidence: 99%
“…With the decline in chlorophyll concentration as the season advanced towards autumn, phospholipids, triacylglycerols and wax esters dominated the lipid material in the traps. Change in POM and DOM lipid composition from a glycolipidsdominated lipid pool, to a neutral (wax esters, triacylglycerols) and phospholipids-dominated lipid pool, has already been observed in ecosystems changing from micro-and or pico-phytoplankton to heterotrophs-dominated regimes (Smith et al, 1997;Goutx et al, 2000;Ghiglione et al, 2007;Bourguet et al, 2008). During DYNAPROC 2, a similar shift occurred in the suspended particles and dissolved matter .…”
Section: Links Between Production Regime and Fluxes; Comparison With mentioning
confidence: 78%
“…Abundant researches carried out in marine and deep lakes showed that attached bacteria were always less abundant and less diverse but generally more active than free-living bacteria (Ghiglione et al 2007, Grossart et al 2003b, Simon et al 2002. Using 16S ribosomal desoxynucleic acid (rDNA) based clone library analysis, however, we found that in shallow productive eutrophic Lake Taihu, OA harbors diverse bacterial clusters (Tang et al 2010).…”
Section: The Diversity Of Attached Bacteria Vs Free-living Bacteriamentioning
confidence: 91%